KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH UNGGUL BERBASIS DIGITAL DI GUGUS I BILAH HULU - Faisal Efendi Siregar; Iwan Purnama; Sakinah Ubudiyah Siregar; Marlina Siregar; Aziddin Harahap (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The rapid development of digital technology requires the education sector to transform toward an innovative and adaptive system, making the role of the principal as a visionary leader crucial in improving teacher performance and implementing digital-based learning. This study aims to analyze the role of visionary leadership of the principal, identify the challenges encountered, and examine the strategies implemented in realizing a digitally superior school at SD Negeri 43 Bilah Hulu. This research employed a descriptive qualitative approach with a field research design. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. The results show that the principal’s visionary leadership plays a significant role in improving teacher performance through role modeling, inspirational motivation, intellectual stimulation, and individualized consideration. However, several challenges were identified, including limited technological infrastructure, disparities in teachers’ digital competencies, and difficulties in implementing adaptive and fair policies. To address these challenges, the principal implemented strategies such as strengthening collaborative leadership, improving the quality of technology-based learning, enhancing teacher competence and professionalism, promoting student achievement, and gradually providing adequate facilities and infrastructure. Thus, it can be emphasized that the principal’s visionary leadership is a key factor in realizing a digitally-based excellent school, as the success of educational transformation is determined not only by the availability of technology, but more importantly by the quality of leadership and the readiness of human resources to manage and optimize it. ABSTRAK Perkembangan teknologi digital menuntut dunia pendidikan untuk bertransformasi menuju sistem yang inovatif dan adaptif, sehingga peran kepala sekolah sebagai pemimpin visioner menjadi sangat penting dalam mendorong peningkatan kinerja guru dan implementasi pembelajaran berbasis digital. Penelitian ini bertujuan untuk menganalisis peran kepemimpinan visioner kepala sekolah, mengidentifikasi hambatan yang dihadapi, serta mengkaji strategi yang diterapkan dalam mewujudkan sekolah unggul berbasis digital di SD Negeri 43 Bilah Hulu. Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian lapangan (field research). Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman yang meliputi kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan visioner kepala sekolah berperan signifikan dalam meningkatkan kinerja guru melalui keteladanan, motivasi, stimulasi intelektual, dan perhatian individual. Namun, terdapat hambatan berupa keterbatasan sarana prasarana teknologi, ketimpangan kompetensi digital guru, serta tantangan dalam penerapan kebijakan yang adaptif dan adil. Untuk mengatasi hambatan tersebut, kepala sekolah menerapkan strategi berupa penguatan kepemimpinan kolaboratif, peningkatan mutu pembelajaran berbasis teknologi, pengembangan kompetensi dan profesionalisme guru, peningkatan prestasi siswa, serta penyediaan sarana prasarana secara bertahap. Dengan demikian, dapat ditegaskan bahwa kepemimpinan visioner kepala sekolah merupakan faktor kunci dalam mewujudkan sekolah unggul berbasis digital, karena keberhasilan transformasi pendidikan tidak hanya ditentukan oleh ketersediaan teknologi, tetapi terutama oleh kualitas kepemimpinan dan kesiapan sumber daya manusia dalam mengelola serta mengoptimalkannya.